Pengaruh Jumlah Anggota, Modal Luar, Volume Usaha, dan Total Aset terhadap Pendapatan Sisa Hasil Usaha Koperasi di Provinsi Bali Tahun 2015-2020 - Fahrian Hanantha Ihza Fitratama; Hadi Sumarsono (Universitas Proklamasi 45, 2023)
Cooperatives can play a role as one of the main forces in encouraging national economic growth. One of the indicators in improving the welfare of members can be proven by the increase in SHU. This study aims to examine how the independent variables (number of members, external capital, business volume, and total assets) can affect the dependent variable (SHU) in all cooperatives in Bali Province. The approach in this study is a quantitative approach with a verification method using panel data regression analysis. This study uses secondary data with time series 2015-2020 and a cross-section of 9 districts/cities sourced from the publications of the Bali Province Cooperatives and UMKM Office. It’s known that the results of this study when proven simultaneously, that the external capital variable, business volume variable, and total asset variable have a significant influence on the SHU variable. Partially it’s known that the variable number of members has no influence and is negatively related to the SHU variable, there is a significant influence between external capital and the SHU variable but is negatively related, the business volume variable has a significant and positive relationship to the SHU variable, and the total assets variable has an influence as well significantly related to the SHU variable.